ChemInform Abstract: Fully and Partially Li‐Stuffed Diamond Polytypes with Ag—Ge Structures: Li2AgGe and Li2.53AgGe2. Issue 16 (April 2015) - Henze, Alexander; Hlukhyy, Viktor; Faessler, Thomas F.
Abstract The Li‐Ag‐Ge phase diagram is studied.